Assessment of Sand Dune Hazards for Land Use/Land cover in Ma’an Governorate - AL-Taani, Aymen; Al-husban, Yusra (Opción, 2019)
The main goals of this paper are to assess the risk of sand accumulation as a hazard for the land use/land cover (LULC) in Ma’an Governorate via comparative quantitative research methods. The results of LULC showed that human activities represent only 340.74 km² (1.03%), namely of built-up area, forest and irrigated area, besides the 240 km of road length concentrated in the western and southwestern regions of Ma’an, so the sand accumulation is hazards well-studied in detail in this area. In conclusion, many farms were relocated from one place to another to avoid areas covered by sand dunes.